Direct ink writing of SiOC ceramics with microwave absorption properties. Issue 8 (15th April 2023) - Miao, Yalan; Wang, Guantong; Gong, Hongyu; Sheng, Mingming; Jing, Jie; Lu, Junbin; Liu, Maoyun
Abstract: SiOC ceramics have been considered one of the most promising materials in the field of microwave absorbing materials. When SiOC ceramics are prepared by polymer precursor conversion, chemical modification to improve microwave absorption performance is generally carried out in the precursor preparation and molding process. To meet the requirements of more application scenarios, direct ink writing, one of the 3D printing technologies with more flexible structure and shape design is used to replace the traditional molding methods. In this study, the key problems of the combination of direct ink writing and polymer precursor conversion were solved, and SiOC microwave absorbing ceramics with good structure and shape were obtained. After testing, the minimum reflection loss of the ceramics can reach −36 dB, and the corresponding effective absorption band bandwidth is 2 GHz. The experiments confirmed the possibility of combining 3D printing with polymer precursor conversion and its great potential for preparing microwave absorbing ceramics.